2021
DOI: 10.1039/d1nr00708d
|View full text |Cite|
|
Sign up to set email alerts
|

Surface-enhanced Raman spectroscopy for bioanalysis and diagnosis

Abstract: In recent years, bioanalytical surface-enhanced Raman spectroscopy (SERS) has blossomed into a fast-growing research area. We present here a review on SERS-based assays with focus on early bacterial infection detection and chronic disease diagnosis.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
92
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 141 publications
(92 citation statements)
references
References 264 publications
(334 reference statements)
0
92
0
Order By: Relevance
“…In recent years, SERS has been growingly studied and serves as a convenient and non-destructive analytic method in human disease. 13 Combined with metallic nano-substrate, signal intensity of SERS peaks can be enhanced 10 6 to 10 8 times and provide fingerprint information of analyzed samples including blood, urine and saliva, thus enabling biocomponent identification and disease assessment. 29 With its non-destructive nature and convenience, SERS analysis of human specimen has been extensively used in cancer diagnosis and assessment such as prostate cancer, gastric cancer and hepatocellular cancer, which yield high accuracies and promising potentials.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In recent years, SERS has been growingly studied and serves as a convenient and non-destructive analytic method in human disease. 13 Combined with metallic nano-substrate, signal intensity of SERS peaks can be enhanced 10 6 to 10 8 times and provide fingerprint information of analyzed samples including blood, urine and saliva, thus enabling biocomponent identification and disease assessment. 29 With its non-destructive nature and convenience, SERS analysis of human specimen has been extensively used in cancer diagnosis and assessment such as prostate cancer, gastric cancer and hepatocellular cancer, which yield high accuracies and promising potentials.…”
Section: Discussionmentioning
confidence: 99%
“… 12 The convenient process and simple specimen requirement enable SERS to be widely applicated in human malignancy diagnosis and monitoring with high accuracy. 13 A growing number of studies have shown that SERS can reflect biochemical alterations in biospecimens and achieve sensitive and non-invasive diagnosis of multiple malignancies including prostate cancer, breast cancer and lung cancer. 14–16 It has been reported that SERS analysis of blood serum can accurately detect prostate cancer in patients with “gray zone” prostate-specific antigen levels of 4–10 ng/mL with over 90% accuracy.…”
Section: Introductionmentioning
confidence: 99%
“…The unlabeled assay is a Raman spectroscopy of exosomes obtained by adsorbing the purified exosomes directly or very close to the SERS substrate surface ( Soares Martins et al, 2018 ; Zhang et al, 2019b ). The signal intensity in SERS decays exponentially as the analyte moves away from the hot spot ( Liu et al, 2021b ; Tahir et al, 2021 ). To obtain the desired exosome Raman signal, efficient SERS-enhanced substrates need to be prepared.…”
Section: Sers Technology For Exosome Detectionmentioning
confidence: 99%
“…[ 2 , 3 ]). Nowadays, the SERS effect is widely used for detecting target molecules at low concentrations that are important for numerous applications, from ecology [ 4 ] and chemistry [ 5 ] to biosensorics [ 6 , 7 , 8 ], including biomedical diagnostics [ 9 , 10 , 11 , 12 ]. The most convenient explanation of SERS considers two main mechanisms, i.e., (i) electromagnetic enhancement and (ii) chemical one [ 3 ].…”
Section: Introductionmentioning
confidence: 99%